Analysis and evaluation of mortality losses of the 2001 African swine fever outbreak, Ibadan, Nigeria (2007)
The mortality losses of pigs of various age groups affected by the 2001 African swine fever outbreak in Ibadan Nigeria were analyzed and evaluated. Thirty one thousand nine hundred and sixteen (31,916) pigs on three hundred and six (306) farms reported by the Pig Farmers Association of Nigeria and the State Ministry of Agriculture and Natural Resources were involved. Gross mortality was ninety one percent (91%), while age group mortality ranged from 75.9% (growers), 83.1% (weaners), 91.2% (finishers) and 99.8% (piglets); to 100.0% in gilts, sow and boars. Losses were estimated to worth nine hundred and forty one thousand, four hundred and ninety one dollars, sixty seven cents (US $941,491.67). Highest financial loss was from sows (29.5% of total loss), followed by gilts (16.6%), finishers (15.2%), weaners (10.7%), boars (10.6%), growers (10.6%) and piglets (8.2%). Average mortality loss per farm of $3076.77 was of great financial and socioeconomic consequences for a developing country like Nigeria with a low Gross Domestic Product figures. In conclusion, the need to immediately revisit and take recommended actions on the 1998 Report of the FAO Consultancy Mission to Nigeria on Control and Eradication of an Outbreak of African swine fever in Western Nigeria is stressed